FACTORS AFFECTING PURCHASE INTENTION OF HEALTHY DRINKS - Lie, Brenden; Tjokrosaputro, Miharni; Ariniputri, Nadia; Krisnaputra, Ariel; Devotyasto, Mario (International Journal of Application on Economics and Business, 2023)
Today, choosing healthy foods and providing adequate nutrients is crucial for the body. Someone better choose clean foods and beverages that have undergone hygienic processing to prevent contamination with harmful ingredients. One of the products that can assist customers in meeting their nutritional needs to increase endurance and avoid illness is healthy beverages. This study examined how health awareness, food safety, and perceived advantages affect the buying intention of healthy drinks. This research employs a non-probability approach with purposive selection. 224 respondents were recruited by disseminating surveys online via Google Forms, and the data was evaluated using SmartPLS4.0-SEM. The results of this study show that health consciousness, food safety, and perceived benefits all have positive but minor effects on purchase intentions for healthy beverages in Jakarta. The results of this study suggest that food safety and health consciousness can increase consumer demand for healthful drinking products. Therefore, healthy drinks can pay attention to these factors to increase consumer interest in buying healthy beverage products.